Elicitation of Norwegian EQ-5D-5L values for hypothetical and experience-based health states based on the EuroQol Valuation Technology (EQ-VT) protocol. Issue 6 (11th June 2020) - Hansen, Tonya Moen; Helland, Ylva; Augestad, Liv Ariane; Rand, Kim; Stavem, Knut; Garratt, Andrew
Abstract : Introduction: Norway is one of several European countries that lacks a national value set and scoring algorithm for the EuroQol five dimensions (EQ-5D). Recent studies have found differences between countries in terms of health values or preferences for health states described by instruments such as the EQ-5D. The project aims to model a national value set for the five level version of the EQ-5D based on values elicited from a representative sample of the Norwegian adult general population in terms of region, age, sex and level of education. Using a sampling strategy supporting the collection of values for both hypothetical and experienced health states, the study will have the additional aim of assessing the feasibility of collecting experience-based values in accordance with the latest EQ-5D valuation study protocol, and comparing values with those given for hypothetical health states. Methods and analysis: Multistage random sampling and quota-sampling will contribute to representativeness. To increase the number of valuations of experienced health states, those with less than perfect health will be oversampled, increasing the total number of interviews from 1000 to 1300–1500. The most recent EQ-5D valuation protocol will be followed which includes computer assisted face-to-face, one-to-one interviews and use of composite time trade-off and discrete choice experiments. Ethics and dissemination: The study has been reviewed and found to be outside of the scope of the ethics committee and thus not in need of ethical approval. The study findings will be disseminated through peer-reviewed publications, conference presentations and summaries for key stakeholders and partners in the field. The scoring algorithms will be available for widely used statistical software.